Quantitative and Mechanistic Understanding of AZD1775 Penetration across Human Blood–Brain Barrier in Glioblastoma Patients Using an IVIVE–PBPK Modeling Approach - Li, Jing (Clin Cancer Res, 2017)
PURPOSE: AZD1775, a first-in-class, small-molecule inhibitor of the Wee1 tyrosine kinase, is under evaluation as a potential chemo- and radiosensitizer for treating glioblastoma. This study was to prospectively, quantitatively, and mechanistically investigate the penetration of AZD1775 across the human blood–brain barrier (BBB). EXPERIMENTAL DESIGN: AZD1775 plasma and tumor pharmacokinetics were evaluated in 20 patients with glioblastoma. The drug metabolism, transcellular passive permeability, and interactions with efflux and uptake transporters were determined using human derived in vitro systems. A whole-body physiologically based pharmacokinetic (PBPK) model integrated with a four-compartment permeability-limited brain model was developed for predicting the kinetics of AZD1775 BBB penetration and assessing the factors modulating this process. RESULTS: AZD1775 exhibited good tumor penetration in patients with glioblastoma, with the unbound tumor-to-plasma concentration ratio ranging from 1.3 to 24.4 (median, 3.2). It was a substrate for ABCB1, ABCG2, and OATP1A2, but not for OATP2B1 or OAT3. AZD1775 transcellular passive permeability and active efflux clearance across MDCKII–ABCB1 or MDCKII–ABCG2 cell monolayers were dependent on the basolateral pH. The PBPK model well predicted observed drug plasma and tumor concentrations in patients. The extent and rate of drug BBB penetration were influenced by BBB integrity, efflux and uptake active transporter activity, and drug binding to brain tissue. CONCLUSIONS: In the relatively acidic tumor microenvironment where ABCB1/ABCG2 transporter-mediated efflux clearance is reduced, OATP1A2-mediated active uptake becomes dominant, driving AZD1775 penetration into brain tumor. Variations in the brain tumor regional pH, transporter expression/activity, and BBB integrity collectively contribute to the heterogeneity of AZD1775 penetration into brain tumors.